An investigative study of students' attitudes toward computers at Yio Chu Kang Secondary School - Katijah Mohd Nathar. (2008)
Since the implementation of Computer Applications to the Normal Technical Stream students in secondary schools by the Ministry of Education in 1994, Yio Chu Kang has introduced Computer Education to the Express and Normal Academic students as Enrichment Programmes. Furthermore, the school is in the Second Phase of the Ministry of Education Masterplan for IT in Education. No study was conducted to find out students' attitudes toward computers. At the organisational level, knowledge of how students respond to computers in relation to their importance as tools for learning, life, entertainment and communication, and students' confidence in their ability to use computers would therefore be useful information for planning and organising future computer education programmes. Thus the general purpose of this research was to investigate how students cope with the computer courses offered by the school, and measure their attitudes and confidence toward computers.